2021
DOI: 10.1039/d1qi00542a
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium carbonyl complexes bearing methylated triphenylphosphonium cations as antibody-free mitochondria trackers for X-ray fluorescence imaging

Abstract: Synchrotron Radiation X-ray Fluorescence (SXRF) imaging is a powerful technique for the visualization of metal complexes in biological systems. However, due to the lack of an endogenous elemental signature for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…A copper catalyzed azide alkyne cycloaddition (CuAAC) between compound 7 and ethynyl pyridine 8 followed by counter ion exchange (iodide to chloride) on resin generated the pyridine−triazole (pyta) ligand 9 . The rhenium tricarbonyl complex TP−RePyta was finally obtained using rhenium pentacarbonyl chloride in classical coordination conditions [20,26] …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A copper catalyzed azide alkyne cycloaddition (CuAAC) between compound 7 and ethynyl pyridine 8 followed by counter ion exchange (iodide to chloride) on resin generated the pyridine−triazole (pyta) ligand 9 . The rhenium tricarbonyl complex TP−RePyta was finally obtained using rhenium pentacarbonyl chloride in classical coordination conditions [20,26] …”
Section: Resultsmentioning
confidence: 99%
“…The conjugation of TPÀ 2Bzim with the ReÀ Pyta moiety seems detrimental to the mitochondrial targeting. This is quite unexpected as recent work from Bertrand et al [20] demonstrated that the conjugation of a ReÀ Pyta probe with triphenyl phosphonium (TPP) cations retained the mitochondrial targeting of these TPPs. We then conducted colocalization experiments with both probes and LysoTracker Red.…”
Section: Mitochondrial Localization and Internalization Mechanism Of ...mentioning
confidence: 97%
See 3 more Smart Citations